If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.14 + -0.01(x + 1) = -0.04(3 + -1x) Reorder the terms: 0.14 + -0.01(1 + x) = -0.04(3 + -1x) 0.14 + (1 * -0.01 + x * -0.01) = -0.04(3 + -1x) 0.14 + (-0.01 + -0.01x) = -0.04(3 + -1x) Combine like terms: 0.14 + -0.01 = 0.13 0.13 + -0.01x = -0.04(3 + -1x) 0.13 + -0.01x = (3 * -0.04 + -1x * -0.04) 0.13 + -0.01x = (-0.12 + 0.04x) Solving 0.13 + -0.01x = -0.12 + 0.04x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.04x' to each side of the equation. 0.13 + -0.01x + -0.04x = -0.12 + 0.04x + -0.04x Combine like terms: -0.01x + -0.04x = -0.05x 0.13 + -0.05x = -0.12 + 0.04x + -0.04x Combine like terms: 0.04x + -0.04x = 0.00 0.13 + -0.05x = -0.12 + 0.00 0.13 + -0.05x = -0.12 Add '-0.13' to each side of the equation. 0.13 + -0.13 + -0.05x = -0.12 + -0.13 Combine like terms: 0.13 + -0.13 = 0.00 0.00 + -0.05x = -0.12 + -0.13 -0.05x = -0.12 + -0.13 Combine like terms: -0.12 + -0.13 = -0.25 -0.05x = -0.25 Divide each side by '-0.05'. x = 5 Simplifying x = 5
| 5x-7=34x | | 10x-10y=-10 | | 5x^2-(3x^3+2x-6)-4x^3(x^2-4)= | | x+x+1= | | -18+9y=-54 | | -3(2p-3)=-33+p | | 3(p+1)+7(p-6)=-19 | | -48=6u+12 | | 48+8r= | | 4(x-2)-12= | | 27x^3+343= | | 9y+9-5y=1 | | 1200=1.5X+5X | | -9(-1d-4)-4d=31 | | -3(x+1)+7(3-2x)=18 | | 8+14x=16x+-2 | | 11x^5+43x^4+7x^3-133x^2-120x+12=0 | | x+2.75=6.5 | | 60x+5= | | 1.8x+1.4y=21 | | -x=0.4 | | 8-3(2x+5)=4x+10 | | -23+3=m-4 | | 10=3(1-2b)-(3-8b) | | -2(1+b)=(b-8)-3 | | 10m-45=5+10(2m-1) | | -4a-5(-3a-16)=14 | | 0=x^2+24+180 | | -9z^2+18z-58=0 | | 6x^2-486= | | 7(4-7x)+7x=-266 | | 43=7-4x |